Effect of addition of ceramic granules on compressive Strength Concrete - Anita Setyowati Srie Gunarti; Ninik Paiyati; Ratna Ningrum Aflfandi (Lembaga Penelitian dan Pengabdian Masyarakat Universitas Islam 45, 2010)
Future technological developments are now demanding concrete action to improve the performance of concrete produced, both in terms of quality, materials and how to apply, it is not free from the demands and needs of the community towards a more advanced infrastructure facilities. It is therefore necessary to find an alternative as the base material is replaced with a grain of sand concrete waste ceramics. Attempts to utilize the waste form ceramic grains will not only reduce environmental problems but it can provide economic value for development, as well as efforts to conserve natural resources. The study was conducted at the Concrete Laboratory of the University of Islam